Where Has All the R-process Gone? Timescales for Gamma-Ray Burst Kilonovae to Enrich Their Host Galaxies - Anya E. Nugent; Alexander P. Ji; Wen-fai Fong; Hilay Shah; Freeke van de Voort (The Astrophysical Journal)
Neutron star (NS) mergers are currently the only observed source of r -process production in the Universe. Yet, it is unclear how much r -process mass from these mergers is incorporated into star-forming gas to enrich stars. This is crucial to consider as all other r -process mass estimates in the Universe beyond Earth are based on stellar r -process abundances. Here, we explore the extent to which merger location and host-galaxy properties affect the incorporation of r -process elements into star-forming gas, and quantify an “enrichment” timescale to account for this process. To put this timescale in context, we analyze a population of 12 gamma-ray bursts (GRBs) with probable associations to r -process kilonovae (GRB-KNe) and 74 short GRBs without claimed KNe, including new nonparametric star formation histories for the GRB-KN hosts. We find the enrichment timescales for this sample are between ​​​​​​≈7 Myr and 1.6 Gyr, suggesting that environmental enrichment is delayed from NS merger occurrence. Moreover, we find a correlation between the amount of environmental enrichment from a single event and increasing host specific star formation rate (sSFR), and little correlation with stellar mass and GRB galactocentric offset. Environments with low sSFRs (<10 ^−10.5 yr ^−1 ), which comprise 18% of short-GRB hosts and the host of GW170817, will have little to no capacity for stellar enrichment. Our results indicate that not all r -process from NS mergers is incorporated into newly forming stars, and instead some remains “lost” to the circumgalactic medium or intergalactic medium. Future studies should consider these losses to understand the total contribution from NS mergers to the Universe’s r -process budget.